Determination of Factors Influencing Compliance with the Use of Personal Protective Equipment (PPE) Among Cleaning Staff at the Puuwatu Landfill in Kendari City - Aceng, Aceng Yunisar; Hamiru, La Ode; Armayani, Armayani (Miracle Journal of Public Health, 2025)
Garbage workers are workers in one of the informal sectors that are at risk of exposure to diseases caused by garbage. Based on preliminary data collected by researchers from 10 Landfill sanitation workers, it was found that only 3 workers used PPE completely, 5 workers had low knowledge, and 4 workers had low attitudes. This study aims to determine the factors associated with the use of personal protective equipment (PPE) among Landfill sanitation workers in Puuwatu, Kendari City. This is a quantitative study with a cross-sectional design. The population in this study consisted of 66 workers, with a sample of 36 respondents selected using simple random sampling. The data were analyzed using univariate and bivariate analysis with the Chi-Square test. The results of this study show a moderate relationship between knowledge (X2 count=8.371), a moderate relationship between attitude (X2 count=11.638), a moderate relationship between the availability of PPE (X2 count=8.377), and the use of Personal Protective Equipment (PPE) among sanitation workers at the Puuwatu Landfill in Kendari City. It is recommended that sanitation workers improve their knowledge and attitudes and instill in themselves that the use of PPE is a necessity at work.